Quantitative and Qualitative Characterization of Coatings Added to Low Voltage Switches - Troudi, Leila; Jelassi, Khaled (Advances in Technology Innovation, 2022)
Electroplating is one of the most important processes in the manufacturing of switches. Coating the conductive parts of switches improves their appearance and increases their durability, even in severe environments. This study proposes a non-destructive testing method to qualitatively and quantitatively characterize coatings added to the conductive parts of low voltage switches (contacts and terminals). The method is based on the injection of a high-frequency signal into a switch using the vector network analyzer (VNA). An in-depth analysis of the reflected signal is conducted to characterize the coatings. For the quantitative characterization, a comparison is made between switches that are plated with different coating thicknesses. As for the qualitative characterization, a comparison is made between switches that are manufactured with different types of metals. The results show that each switch type has an electromagnetic signature that varies according to the conductivity and the thickness of the metals used for coating.